Título Padrão: a importância do acervo das pedras litográficas para o Núcleo de Arte Contemporânea da Universidade Federal da Paraíba (NAC/UFPB) - Ribeiro, Thiago Alves; Lima, Geysa Flávia Câmara de; Santos, Lucas Lima (Informação em Pauta, 2023)
The present article aims to present the forms of documentation/works of the collection of lithographic stones of the Núcleo de Arte Contemporânea da Universidade Federal da Paraíba (NAC/UFPB) and to establish the context in which these images were produced, starting with the technique itself: lithography. Our methodological approach is based on bibliographic and descriptive research, and addresses a subject that has been little studied in the Archival field, and is therefore of an exploratory nature. We find that, in the face of the diversity of information and with the development of different techniques and methods of document organization, we are faced with a collection of lithographic stones that is almost totally abandoned. Thus, we list in general terms the situation of the collection of lithographic stones of the NAC/UFPB, as it is a silenced and forgotten space, but its archives and relics are of utmost importance for our society and trajectory. We conclude that the need to preserve the documentation stored in the archives is perceptible, since public documents can and should be accessible to society. However, it is essential that the State intervenes in terms of organization and safeguarding, to subsequently make the collection accessible.